2011
DOI: 10.1111/j.1466-8238.2011.00727.x
|View full text |Cite
|
Sign up to set email alerts
|

The biogeography and filtering of woody plant functional diversity in North and South America

Abstract: AimIn recent years evidence has accumulated that plant species are differentially sorted from regional assemblages into local assemblages along local-scale environmental gradients on the basis of their function and abiotic filtering. The favourability hypothesis in biogeography proposes that in climatically difficult regions abiotic filtering should produce a regional assemblage that is less functionally diverse than that expected given the species richness and the global pool of traits. Thus it seems likely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

42
337
14
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 265 publications
(404 citation statements)
references
References 52 publications
42
337
14
2
Order By: Relevance
“…This analysis builds on previous analyses that showed significant trait convergence (22) for several biomes, which was attributed to environmental differences (16,23,24). These studies also suggest that the functional differences among communities can be conveniently represented by community mean trait values (25).…”
Section: Resultsmentioning
confidence: 76%
“…This analysis builds on previous analyses that showed significant trait convergence (22) for several biomes, which was attributed to environmental differences (16,23,24). These studies also suggest that the functional differences among communities can be conveniently represented by community mean trait values (25).…”
Section: Resultsmentioning
confidence: 76%
“…It has been shown that using trait distributions leads to different estimates of carbon dynamics (32) and that higher-order moments of trait distributions contribute to sustaining multiple ecosystem functions (33). While species-level mapping (21,23,24) does capture trait distributions, it has been limited geographically and restricted to subsets of functional groups.…”
Section: Significancementioning
confidence: 99%
“…Previous work has extrapolated trait measurements across continental or larger regions through three methodologies: (i) grouping measurements of individuals into larger categories that share a set of properties [a working definition of plant functional types (PFTs)] (4, 15), (ii) exploiting trait-environment relationships (e.g., leaf Nm and mean annual temperature) (1,(16)(17)(18)(19)(20), or (iii) restricting the analysis to species whose presence has been widely estimated on the ground (21)(22)(23)(24). Each of these methods has limitations-for example, trait-environment relationships do not well explain observed trait spatial patterns (1,25), while species-based approaches limit the scope of extrapolation to only areas with well-measured species abundance.…”
mentioning
confidence: 99%
“…Studies have considered the adaptive mechanisms behind strategies within a single ecosystem, including predator avoidance, energetic constraints, diet quality, and interspecific competition (9,21). Meanwhile, although mapping functional traits has become a core technique in functional biogeography (22,23), surprisingly little is known about the biogeography of diel activity patterns, and the extent to which they are determined by geographic gradients in light and climate. Addressing such issues has become more pressing with growth in the evidence for a wide range of ecological impacts of both anthropogenic climatic change and nighttime light pollution (24)(25)(26)(27)(28).…”
mentioning
confidence: 99%